Posttraumatic growth and suicide risk in college students according to trauma type: a failure to replicate - Sheline, Kelly T., author; Rosén, Lee A., advisor; Swaim, Randall C., committee member; Rickard, Kathryn, committee member; Biringen, Zeynep, committee member (Colorado State University. Libraries, 2015)
While numerous studies have demonstrated that different types of traumatic life events predict differences in PTSD symptoms, there is a lack of research examining if posttraumatic growth also varies based on trauma type. This study investigated both positive posttrauma changes as measured by the Posttraumatic Growth Inventory (PTGI; Tedeschi & Calhoun, 1996) and negative changes as measured by suicide risk and suicidal ideation and behavior in 335 college student survivors of three distinct traumatic event types: bereavement, chronic or acute illness, and accidental injury. The results showed that there was not a statistically significant difference in the total PTGI score or the PTGI subscale scores for the three trauma groups. There was not a significant difference between traumatic events on suicide risk and suicidal ideation and behavior. Posttraumatic growth did not moderate the relationship between type of trauma and suicide risk. Several plausible explanations for these results are explored in the discussion, including the role of event centrality and homogeneity of the sample.
Keywords: posttraumatic growth; trauma; suicide; college students